Outcome of bowel function following anterior resection for rectal cancer-an analysis using the low anterior resection syndrome (LARS) score - Kupsch, Juliane; Jackisch, Thomas; Matzel, Klaus E.; Zimmer, Joerg; Schreiber, Andreas; Sims, Anja; Witzigmann, Helmut; Stelzner, Sigmar (International Journal of Colorectal Disease, 2018)
PURPOSE: Severity of anorectal dysfunction after low anterior resection is associated with various patient- and treatment-related factors. We aimed to quantify anorectal dysfunction after treatment for rectal cancer using the low anterior resection syndrome (LARS) score. METHODS: We retrieved from a prospective database 331 eligible patients on whom anterior resection for rectal cancer had been performed from 2000 to 2014. All patients were sent a LARS score accompanied by a supplementary questionnaire. Response rate was 78.8% (261 patients). The main outcome measure was the relation of the LARS score to potentially associated patient and treatment factors. Secondary endpoints were further measures that reflect anorectal dysfunction, e.g., Vaizey score. RESULTS: Overall, 144 (55.2%) patients exhibited scores > 20 reflecting minor (n = 51 (19.5%)) or major (n = 93 (35.6%)) LARS. A significant difference for scores > 20 was found for intersphincteric resection (IR, 73.2% affected patients) compared to total mesorectal excision (TME, 58.4%) and partial mesorectal excision (PME, 38.0%, p = 0.001). Radio(chemo)therapy resulted in LARS scores > 20 in 64.6% of patients compared to 43.1% in patients without irradiation (p = 0.001). Type of procedure (TME and IR as compared to PME), radio(chemo)therapy, and younger age were independently associated with LARS in logistic regression analysis. However, younger age remained the only independent factor for higher scores after exclusion of PME. CONCLUSIONS: The LARS score identified a substantial proportion of patients after surgery for rectal cancer with anorectal dysfunction. The extent of surgical procedure is independently associated with the severity of symptoms whereas the role of radiotherapy needs further assessment.
EVALuna2:34499